1996
DOI: 10.1093/oxfordjournals.humrep.a019264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clomiphene citrate stimulation on endometrial structure in infertile women

Abstract: Investigations into the effect of clomiphene citrate stimulation on endometrial differentiation were retrospectively performed in the mid-luteal phase on 21 patients undergoing ovulation induction prior to artificial insemination. A high incidence of irregular endometrial development was seen using morphological and morphometric criteria; in addition, increasing stromal oedema after clomiphene citrate treatment was observed. Measurable differences in glandular development (i.e. numbers of glands and glandular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Clomiphene has been shown to reduce the number of estrogen and progesterone receptors and glandular density in the endometrium, and increase the number of vacuolated cells (6,8). All of these features are consistent with a hypoestrogenic effect (5).…”
Section: Effect Of Clomiphene Citratementioning
confidence: 97%
See 1 more Smart Citation
“…Clomiphene has been shown to reduce the number of estrogen and progesterone receptors and glandular density in the endometrium, and increase the number of vacuolated cells (6,8). All of these features are consistent with a hypoestrogenic effect (5).…”
Section: Effect Of Clomiphene Citratementioning
confidence: 97%
“…It is easily administered, has relatively few side effects, and the risk of multiple pregnancy is relatively low. The mechanism of action is as an anti-estrogen agent exerting effects on the hypothalamus, pituitary, and uterus (5)(6)(7)(8). Of clinical importance is the effect of CC on endometrial thickness and quality as detected sonographically.…”
Section: Introductionmentioning
confidence: 99%
“…However, CC has been associated with lower pregnancy rates (15%) and a higher likelihood of miscarriage (18), suggesting that CC may adversely affect the endometrial receptivity (19). High-throughput DNA microarray techniques have demonstrated that human endometrium undergoes programmatic changes in gene expression throughout the menstrual cycle that can become dysfunctional in certain conditions such as endometriosis (11).…”
mentioning
confidence: 99%
“…This differential protein response to estrogen can perhaps be explained in the light of antiestrogenic influence of CC at the target tissues (26,27). It is possible that CC exerted its antagonistic effect at the endometrial level (2) and attenuated the uterine production of 64.0-kDa protein.…”
Section: Discussionmentioning
confidence: 99%